Translational potential of a mouse in vitro bioassay in predicting gastrointestinal adverse drug reactions in Phase I clinical trials. Issue 7 (11th May 2014) - Keating, C.; Ewart, L.; Grundy, L.; Valentin, J.P.; Grundy, D.
Abstract Background Motility‐related gastrointestinal (GI) adverse drug reactions (GADRs) such as diarrhea and constipation are a common and deleterious feature associated with drug development. Novel biomarkers of GI function are therefore required to aid decision making on the GI liability of compounds in development. Methods Fifteen compounds associated with or without clinical GADRs were used to assess the ability of an in vitro colonic motility bioassay to predict motility‐related GADRs. Compounds were examined in a blinded fashion for their effects on mouse colonic peristaltic motor complexes in vitro. For each compound concentration‐response relationships were determined and the results compared to clinical data. Compounds were also assessed using GI transit measurements obtained using an in vivo rat charcoal meal model. Key Results Within a clinically relevant dosing range, the in vitro assay identified five true and three false positives, four true and three false negatives, which gave a predictive capacity of 60%. The in vivo assay detected four true and four false positives, four false and three true negatives, giving rise to a predictive capacity for this model of 47%. Conclusions & Inferences Overall these results imply that both assays are poor predictors of GADRs. Further analysis would benefit from a larger compound set, but the data show a clear need for improved models for use in safety pharmacology assessment of GI motility.